THE PROBLEM OF HALITOSIS WHEN USING REMOVABLE DENTURES (CLINICAL CASE) - V.M. Sokolovska (Український стоматологічний альманах, 2023)
Recently, more and more publications are appeared in the literature in relation to the occurrence of the problem of bad breath, which are based on the basis of scientific researches.